2018
DOI: 10.5935/0103-507x.20180058
|View full text |Cite
|
Sign up to set email alerts
|

Existing capacity for renal replacement therapy and site-specific practices for managing acute kidney injury at centers participating in the BaSICS trial

Abstract: ObjectiveTo investigate the existing capacity for renal replacement therapy and site-specific practices for managing acute kidney injury at centers participating in the BaSICS trial.MethodsA questionnaire was provided to the chairs of 61 intensive care units enrolled in a randomized clinical trial in Brazil. A total of 124 physicians completed the questionnaire.ResultsApproximately 15% of the patients admitted to the analyzed intensive care units received renal replacement therapy at the time of data collectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Regardless of these limitations, our study showed that the variables applied by the Regulation Center that services the Federal District were able to triage patients with a higher chance to benefit from ICU-RRT admission, reinforcing the need for improvement in the ICU-RRT triage and rationing processes. Besides, the shortage of ICU resources, especially RRT support, is a critical problem in several countries, especially in those with a low- and middle-income 6 , 51 , 52 . In Brazil, the poorest or less-educated patients who depend exclusively on the public health system are the most affected, as most Brazilian middle- and higher-income residents have a private health insurance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regardless of these limitations, our study showed that the variables applied by the Regulation Center that services the Federal District were able to triage patients with a higher chance to benefit from ICU-RRT admission, reinforcing the need for improvement in the ICU-RRT triage and rationing processes. Besides, the shortage of ICU resources, especially RRT support, is a critical problem in several countries, especially in those with a low- and middle-income 6 , 51 , 52 . In Brazil, the poorest or less-educated patients who depend exclusively on the public health system are the most affected, as most Brazilian middle- and higher-income residents have a private health insurance.…”
Section: Discussionmentioning
confidence: 99%
“…The shortage of intensive care unit (ICU) resources, including equipment and supplies for renal replacement therapy (RRT), is a critical problem in several countries 1 8 even before the COVID-19 pandemic, drawing attention to the limited capacity of resources in ICU settings worldwide 9 17 . The demand for ICU beds with RRT support (ICU-RRT) exceeding the available capacity is a crucial issue in Brazil, mainly in public hospitals, postponing ICU admission and the RRT initiation 6 and affecting outcomes, such as hospital length of stay and mortality 18 – 23 .…”
Section: Introductionmentioning
confidence: 99%